Effect of nitrogen limitation on growth, total lipid accumulation and protein amount in Scenedesmus acutus as biofuel reactor candidate - Agirman, Nur; Cetin, Ahmet (Zafer AKAN [EN], 2017)
Objective: In this study effects of nitrogen limitation on growth, total lipid and protein amount in Scenedesmus acutus.Material and Methods: The microalgal strain of Scenedesmus acutus used in this study was isolated from the Keban Reservoir in Eastern Anatolia, Turkey was grown in Jaworsky’s medium. Algal cells were calculated by measuring the optical density at 680 nm using a visible density spectrophotometer. The total lipid content was determined using the Bligh and Dyer method. The total protein content was determined by the Lowry method.Results: The results show that there is an inverse relationship between cellular growth, lipid amount and nitrogen concentration. S. acutus survived all the nitrogen concentrations tested and increases were observed in the amount of its cellular lipid. It was determined that there was enough nitrogen in the nitrogen-limited media to support protein synthesis and cell growth of S. acutus and that the amount of lipid in the 50% nitrogen-limited media was 19.48% higher than that in the control group.Conclusion: S. acutus survived all the nitrogen concentrations tested and increases were observed in the amount of its cellular lipid. Significant increase in the amount of lipid in Scenedesmus acutus subjected to nitrogen stress suggests the idea that the microalga in question can be one of the potential organisms that can be used to obtain biofuel.